Influence of VEGF deprivation upon vascular formation by endothelium in the presence of macrophages - A. R. Kozyreva; T. Yu. Lvova; K. L. Markova; A. S. Simbirtsev; A. M. Ischenko; S. A. Selkov; D. I. Sokolov (Медицинская иммунология)
Development of angiogenesis depends on the functional state of endothelial cells, as well as on the balanced secretion of cytokines, growth factors and chemokines by endothelial cells and cells of microenvironment. Macrophages represent an essential component of the microenvironment and take part in the formation of blood vessels both due to the production of cytokines and due to contact interactions with endothelial cells. VEGF is among the most important cytokines that control angiogenesis at all its stages. Currently, the role of VEGF in the intercellular interactions of endothelial cells and macrophages is not well described. The aim of our study was to investigate the effect of VEGF deprivation using monoclonal antibodies on angiogenesis under conditions of co-cultivation of endothelium and macrophages. Materials and methods: monoclonal antibodies to VEGF-A were used for VEGF deprivation in monoculture of endothelial cells and in co-culture of endothelial cells with macrophages. The IL-1β, IL-6 and TNFα cytokines were used as inducers. When VEGF-A was removed from the medium, endothelial cells show plasticity and form longer vessels, they modify the expression of VEGF receptors. Macrophages regulate endothelial cell activity through the secretion of cytokines, including VEGF, and through contact interactions with endothelial cells. THP-1 cells increase the sensitivity of endothelial cells to VEGF by stimulating the VEGFR1 and VEGFR3 expression, this effect is VEGF-A-independent. The IL-1β, IL-6, TNFa cytokines independently stimulate non-branching angiogenesis, increasing the length of the vessels. At the same time, IL-ip increases the VEGFR1 expression on the surface of endothelial cells. In contrast, IL-6 and TNFα decrease it, thereby regulating the sensitivity of endothelial cells to VEGF. The effects of these cytokines are not dependent on VEGF-A. The IL-1β, IL-6, TNFα cytokines promote acquisition of anti-angiogenic properties by THP-1 cells that is independent on VEGF-A, as well as on expression of its receptors by endothelial cells. Thus, VEGF is an important, but not the sole factor controlling angiogenesis. Under conditions of VEGF-A deficiency, either endothelial cells or microenvironment cells are able to compensate for its functional load due to the production of other growth factors.